The "Other Side of The Fence": A Learning- And Control-Based Investigation Of The Relationship Between Deviance And Friendship Quality. Issue 12 (2nd December 2019) - Boman IV, John H.; Agnich, Laura; Miller, Bryan Lee; Stogner, John M.; Mowen, Thomas J.
ABSTRACT: Utilizing frameworks of social control and differential association theories, this study addresses the extent to which deviance (a predictor) is related to friendship quality (the outcome). Using dyadic data, results demonstrate that the highest estimates of friendship quality come from actors who have non-deviant friends and who also refrain from theft and violence themselves. Shared deviance within the friendship, referred to as 'homophily, ' harms friendship quality, although it does not mediate or moderate the deviance – friendship quality link. Overall, deviance relates to friendship quality in a way that supports a bonding tradition more than a learning tradition.